Invasive Streptococcus pneumoniae Infection Causing Hemolytic Uremic Syndrome in Children: Two Recent Cases - Otto G Vanderkooi; James D Kellner; Andrew W Wade; Tajdin Jadavji; Julian P Midgley; Thomas Louie; Gregory J Tyrrell (Canadian Journal of Infectious Diseases)
INTRODUCTION: Streptococcus pneumoniae is an uncommon cause of hemolytic uremic syndrome (HUS) with a unique pathophysiology that differs from Shiga toxin-related HUS.